PENGELOLAAN KELAS BERBASIS BUDAYA PADA PEMBELAJARAN SOSIOLOGI DI KELAS XI F2 FASE F SMA NEGERI 3 SIJUNJUNG - Erin Sonia Oktarin; Faishal Yasin; Sri Rahayu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Culture-based classroom management is a strategic approach that emphasizes order, discipline, and character building for students through the internalization of local culture. Culture-based classroom management aligns closely with the principles and direction of the Independent Curriculum, which emphasizes education that shapes students' character according to the local context and strengthens the Pancasila Student Profile. At SMAN 3 Sijunjung, particularly in grade XI F2 Phase F, teachers not only act as educators but also integrate local cultural values into student management efforts.This study aims to analyze and describe how this classroom management is implemented at SMAN 3 Sijunjung, specifically in Sociology lessons in grade XI F2 Phase F. This study used a descriptive qualitative method, relying on in-depth interviews and field observations as data collection techniques. The study subjects included Sociology teachers and grade XI F2 Phase F students at SMAN 3 Sijunjung. The study shows that culture-based classroom management at SMAN 3 Sijunjung is implemented comprehensively through various aspects.Research results indicate that success is evident in various components, including high levels of student discipline, active participation in learning activities, their ability to solve problems independently, and the formation of harmonious and supportive relationships between teachers and students. This approach demonstrates that teachers play a role beyond simply imparting knowledge, but also as role models who instill moral values through daily behavior and as facilitators who mobilize students' potential. Students no longer view school as a rigid, rule-based place, but rather as an environment that supports and appreciates their existence. Keywords: SMAN 3 Sijunjung, Classroom Management, Sociology Learning, Culture-Based Learning.